ASCII-character-encoding based PPG compression for tele-monitoring system. (January 2017) - Mukhopadhyay, Sourav Kumar; Ahmad, M. Omair; Swamy, M.N.S.
Graphical abstract: Highlights: ASCII-character-encoding-based low-complexity PPG compression algorithm. Heart-rate calculation from compressed PPG data. Web-application and SMS-based low-cost tele-monitoring system. Inherent signal-encryption capability. Mean-opinion-score (MOS) of the reconstructed signal is found to be 'very good'. Abstract: Photoplethysmogram (PPG) is becoming one of the most important techniques for assessing several vascular parameters, but the area of digitized PPG signal compression still remains largely unexplored. This paper presents an efficient PPG compression algorithm, and is developed on the basis of five major sequential steps: noise elimination through Butterworth low-pass filter, down-sampling, inter-sample difference computation, grouping and American Standard Code for Information Interchange (ASCII) character encoding of reduced dataset. The compressed file is then either uploaded to a Hypertext Preprocessor (PHP)-based web-application or transmitted to doctor's mobile phone in the form of short message service (SMS) depending upon the availability and feasibility of services. Efficiency of the compression algorithm is measured in terms of compression ratio and the performance of the reconstruction protocol is tested through a variety of numerical assessments such as the cross correlation coefficient and percent root mean square difference. As per the gold standard subjective measure, the mean-opinion-score of the reconstructed signal is found to be 'very good'. Finally, heart rate is also calculated with no more than 1.68% error from the compressed data without actually reconstructing the signal.